The Training of Fruit Leather Mango Processing in Kaibobu Village, West Seram District, West Seram Regency - Sophia Grace Sipahelut; Vita Novalin Lawalata (Institute for Research and Community Services, 2021)
Mangoes are a widely available type of fruit during the harvest seasons in Kaibobu Village, West Seram, Western Seram Regency, Maluku Province. However, there have been no innovative measures to preserve the mangoes to be consumed outside their harvest seasons. Thus, there should be a training program that focuses on mango processing techniques employed to increase the storability of these mangos while maintaining their nutrient compositions. One such technique is fruit leather. Targeting the family empowerment women groups in Kaibobu Village, the training activities aimed to boost the people’s knowledge and skills in utilizing the potentials of mangoes processed into fruit leather. The activities included both education and training sessions. These community service activities have run well and provided various benefits to the people of Kaibobu Village. The community participation in the program was also evident, as seen from their enthusiasm when they joined both education and training sessions. The participants have garnered more knowledge about mangoes’ nutritional values, technology to process mangoes into fruit leather, and product packaging through the education activities. They also better understood the importance of mango processing and had better skills in processing mangoes into fruit leather. Lastly, the participants received the equipment needed to process their mangoes into fruit leather.